Tempeh attenuates cognitive deficit, antioxidant imbalance, and amyloid β of senescence-accelerated mice by modulating Nrf2 expression via MAPK pathway. (November 2018) - Chan, Yin-Ching; Lee, I-Te; Wang, Ming-Fu; Yeh, Wen-Chin; Liang, Bi-Chun
Graphical abstract: Possible interactive mechanisms of tempeh on improving cognitive deficit in an AD animal model-SAMP8 mice. Highlights: Tempeh improved cognitive ability in an AD animal model. Tempeh decreased MDA and carbonyl protein levels, and increased SOD and CAT activity and mRNA expression. Tempeh decreased Aβ and BACE1 levels. Tempeh enhanced Nrf2 level through MAPK pathway. Abstract: This study investigated the effects of tempeh on the cognitive and antioxidant status in senescence-accelerated mouse prone 8 (SAMP8) mice. Six-month-old SAMP8 mice were divided into one control and three tempeh groups; the tempeh groups were administered 300, 600, and 900 mg/kg body weight (BW) tempeh. The results revealed tempeh groups had stronger cognitive ability, lower malondialdehyde and carbonyl protein levels, and higher superoxide dismutase (SOD) and catalase (CAT) activities in the hippocampus, striatum, and cortex. Of them, the 900 mg/kg BW tempeh showed the most superior results on increasing SOD and CAT mRNA expressions and reducing amyloid β (Aβ) and β-site amyloid precursor protein cleaving enzyme 1 levels; it also increased nuclear factor erythroid 2-related factor 2 (Nrf2) levels by reducing p-p38 and p-JNK expression. In conclusion, tempeh may protect neurons against oxidative stress and Aβ-induced damage and reduce memory impairment by modulating Nrf2 via mitogen-activated protein kinase pathway.